Hoodlum [videorecording (DVD)] - Duke, Bill, 1943-; Fishburne, Laurence, III, 1961-; Roth, Tim; Williams, Vanessa; Garcia, Andy (MGM Home Entertainment, 1998)
In 1930's New York, Bumpy Johnson rules the Harlem numbers racket. When gangster Dutch Schultz threatens his reign, Bumpy realizes that his only way out is a dangerous plan involving mob chieftain Lucky Luciano.